THE OPTIMIZATION OF THE EXPLOSIVE FORCE TRAINING IN VOLLEYBALL - Muresan Alexandru (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
Explosive force conditions the high performance acquisition in volleyball and various other sports. Tests and standards provide information on the effectiveness of control methods, but do not provide enough evidence on the quality of adaptation and future orientation. The scientific literature provides information about research and control equipment. The research aimed the unitary power (PU) on both legs, on the right leg (Pud) and left leg (Pus), the average height of jumps (Hzbor), maximum jump height (Hmax), the difference between the unitary power on both legs and the unitary power on the right and on the left leg. The tests were conducted in October, with two identical devices in two different locations. Data interpretation had as support a reference values kit of performance level offered by one of the inventors of the jumping mat "Miron Georgescu" modified. Correlations between the PU and the other parameters were performed by the SPSS software. The results were graphically represented, analyzed and commented. Analysis of the results revealed that PU interpretation should be nuanced by analysis of body mass index. Low performance was reported in temporarily untrained or injured athletes. The values obtained confirm the need for individualization and fine tuning of power speed ratio in training. Adapting effort to each sport possibilities and coherent guidance to dosing means ensures the health of performers and sports longevity. Using equipment that provides objective and stable information on the status of physical stress caused by exercise is a necessary condition in training programming.